The new century - Salt, Bernard, 1956- (Prahran, Vic. : Hardie Grant Books, 2006)
Articulate, chatty and witty, The Big Picture monitors and interprets those factors that have a bearing on where we live, when we marry and how we work. This is a book that looks at both the minutiae and the motivational forces that shape the Australian community.
Machine derived contents note: PART 1: LIFE -- Values and mores -- The fashion-wave theory: part 1 14 -- The fashion-wave theory: part 2 17 -- Terms of endearment 20 -- Mass market goes pear-shaped 25 -- Television imitates life 29 -- Family ties 32 -- Suburban fashion factories 35 -- Why wedding rings? 38 -- Food as sex for the over-40s 39 -- The domestication of the f-word 43 -- God and the godless 46 -- Ethnic influences on the Australian -- consumer market 49 -- Left brain, right brain 51 -- The beatification of Saint Environment 54 -- It's easy being green: the politics of plastic bags 57 -- Dam you Sydney 60 -- Helicopter kids 64 -- Generations, age and ageing -- Generation X 67 -- Generation Y 71 -- Generation Random 75 -- Factor X and factor Y 79 -- The rise and fall of the empire of the -- baby boomers 82 -- Baby boomer's fashion conspiracy 85 -- Baby boom echo echo 88 -- The flying demographic wedge 90 -- The Tracey factor: why boomers -- and Ys get along 95 -- Generation Y as ethical investors 97 -- Generational ideologies 98 -- Redefining middle age 102 -- The Peter Pan generation 106 -- The new teenage years 110 -- The new teenagers 113 -- Fabulous fifties 115 -- Meet the frugals 117 -- The chaperone syndrome 120 -- Australia and beyond -- The empire of the Australians 124 -- The Australian cultural solar system 128 -- The 'burbs 131 -- The beach 135 -- The bush 138 -- Australian mass market thinks global 141 -- Kiwis teach Aussies bug lesson 145 -- Beware the Kiwification of Australia 148 -- The lucky country's luckiest generation 152 -- PART 2: WORK -- Work and home -- Hot jobs for the new century 156 -- Brave new hi-tech world 159 -- Going where the work is 163 -- From Nerdistan to the Australian Geek Islands 166 -- Job towns 168 -- Your place as the new workplace 172 -- Regional movers shake up Richer scale 175 -- Evolution of the suburban home 179 -- City and suburbia -- Sydney dominates battle of big smokes 183 -- Inner-city groove 186 -- Cultural capital 189 -- Chapel Street, Melbourne 191 -- Melbourne Inc. 193 -- Down to business 194 -- The game 196 -- The Victorian era 200 -- Melbourne as world city 201 -- Ich bin ein coaster 203 -- Lift etiquette: learning the unwritten rules 206 -- Award-winning towns 208 -- Town planners and the urban village myth 212 -- Los Angeles: the scary destination of -- Australian cities 214 -- Towns of the Western District 219 -- Cinderella City: the rise and rise of Brisbane 223 -- A tale of good versus evil 228 -- 2016: a space odyssey 230 -- PART 3: RELATIONSHIPS -- Men and women -- The man drought 236 -- Evolution of time-share men 239 -- The Fella Filter 243 -- The driving force behind relationships 246 -- Liberated women rewrite cultural book 249 -- The rise of the metrosexual 251 -- Loo etiquette 252 -- Women must broaden their market 255 -- New terms needed for new relationships 257 -- Manhattan man-hunters ride the -- subway of love 262 -- The Aussie menopolises 266 -- Sun, surf and the separated 268 -- The Rover syndrome 271 -- Time traveller 273 -- Concluding remarks 277 -- Appendixes 281 -- Table 1 282 -- Table 2 284 -- Table 3 286 -- Select bibliography 288 -- Index 289.
Includes index.
Bibliography: p. 288.
Tertiary/Undergraduate.
Keywords: Australia -- Social conditions